Pollination activity affects selection on floral longevity in the autumnal-flowering plant, Narcissus serotinus L. - Marquéz, I. (2017)
Flower longevity, the period of time that a flower remains open, is a crucial factor in plant reproductive fitness. Though longevity varies substantially among angiosperm species, longer flower longevities may be a selective advantage under unpredictable or scarce pollination activity. This study examined this hypothesis in Narcissus serotinus L. (Amaryllidaceae), a small Mediterranean geophyte that blooms during the autumnal rainy season. Field experiments performed in three natural populations through 3 consecutive years shows that N. serotinus has the ability to expand flower longevity when pollination has not occurred. Flowers that were open longer to pollination have higher reproductive fitness than younger flowers. As N. serotinus flowers age, there was a shift in pollination patterns since flower visits by butterflies became scarcer and are replaced by one small pollen beetle. Given that there was evidence of pollen limitation and that this species produces one single flower, we suggest that extended flower longevity is selected because it assures pollination success under scarce insect visits.